2015
DOI: 10.1017/s0305000915000707
|View full text |Cite
|
Sign up to set email alerts
|

Infants' acceptance of phonotactically illegal word forms as object labels

Abstract: We investigated 16- and 20-month-olds' flexibility in mapping phonotactically illegal words to objects. Using an associative word-learning task, infants were presented with a training phase that either highlighted or did not highlight the referential status of a novel label. Infants were then habituated to two novel objects, each paired with a phonotactically illegal Czech word. When referential cues were provided, 16-, but not 20-month-olds, formed word-object mappings. In the absence of referential cues, inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 26 publications
3
15
0
Order By: Relevance
“…This selectivity is important in more naturalistic word-learning environments when acoustic information may be noisy or inaccessible (due to the presence of background noise, multiple speakers, etc.). Our findings, taken together with prior research observing differences in age (e.g., Hay et al, 2015;Vukatana et al, 2016), vocabulary (e.g., Graf Estes et al, 2011Storkel, 2001), bilingual status , and referential context (Vukatana et al, 2016), reveal that exposure to phonological regularities affects novel word learning; this effect, however, varies based on both the current context and children's past linguistic experiences. Understanding how all of these factors work together has the potential to provide novel insights into possible interventions that might facilitate word learning in children with language disorders.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This selectivity is important in more naturalistic word-learning environments when acoustic information may be noisy or inaccessible (due to the presence of background noise, multiple speakers, etc.). Our findings, taken together with prior research observing differences in age (e.g., Hay et al, 2015;Vukatana et al, 2016), vocabulary (e.g., Graf Estes et al, 2011Storkel, 2001), bilingual status , and referential context (Vukatana et al, 2016), reveal that exposure to phonological regularities affects novel word learning; this effect, however, varies based on both the current context and children's past linguistic experiences. Understanding how all of these factors work together has the potential to provide novel insights into possible interventions that might facilitate word learning in children with language disorders.…”
Section: Discussionsupporting
confidence: 78%
“…Note that these findings are parallel to those described earlier, suggesting group differences such that infants with larger vocabularies have stronger representations of native language phonotactics (e.g., Graf Estes et al, 2016). They are also broadly consistent with evidence suggesting that older infants-who presumably know more about the sound structure of their native language-are less likely to learn words that violate native language phonotactics than younger infants (e.g., Vukatana, Curtin, & Graham, 2016).…”
supporting
confidence: 84%
“…For example, between 12 and 18 months, infants accept nonverbal sounds, pictures, non native clicks, and gestures as potential labels for referents (Curtin, ; May & Werker, ; Namy, ; Namy, Campbell, & Tomasello, ; Namy & Waxman, ; Suanda, Walton, Broesch, Kolkin, & Namy, ). As they develop, infants formulate more stringent expectations about what counts as a word in their language (Graham & Kilbreath, ; May & Werker, ; Suanda & Namy, ; Vukatana, Curtin, & Graham, ), a maturational process that extends at least into the preschool years (Namy et al., ). The course of this maturation has been heavily informed by studies of monolingual children.…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent experiment revealed that 16-month-olds accepted phonotactically illegal labels in a Switch task with referential context (but not without the context). In contrast, 20-month-olds did not learn the illegal labels even after receiving the context cues (Vukatana, Curtin, & Graham, 2016). These findings using the Switch task are broadly consistent with Graf Estes, Edwards, and Saffran’s (2011) findings using another looking-based measure of learning (i.e., looking while listening; Fernald, Zangl, Portillo, & Marchman, 2008).…”
mentioning
confidence: 93%